Disparities in Shared Decision Making and Service Receipt Among Children With Special Health Care Needs and Developmental Delay: A National Survey Analysis. (June 2020) - Perez Jolles, Monica; Zullig, Leah L.; Lee, Pey-Jiuan; Kolhatkar, Gauri
Shared decision making (SDM) is associated with increased service satisfaction among pediatric patients. Our objective was to examine the association between SDM and service use experiences across racial/ethnic child groups. This secondary data analysis used the 2009-2010 National Survey of Children with Special Health Care Needs (CSHCN) and 2011 Pathways to Diagnosis and Services Survey. We used a rank-and-replace matching approach consistent with Institute of Medicine recommendations for health disparities research. We included CSHCN aged 6 to 17 years. The exposure of interest was parents of CSHCN reporting engagement in SDM with clinicians. There were 4032 CSHCN included in analysis. CSHCNs experiencing SDM had a 16% higher probability of reporting service use compared to those not experiencing it (95% CI, 14.24-19.42). Black children experiencing SDM reported seeing all needed care providers at a lower rate than whites (79% and 87.6% respectively; 95% CI, -14.05-3.27). The benefit of SDM over not experiencing it for blacks was 12.2% less than for whites for the outcome of seeing all needed care providers. For the outcome of receiving all needed treatments and services, the SDM benefit was 9.1% lower for Hispanics compared with whites. SDM can improve service experiences but implementation flexibility may be needed.